Application value of the NoSAS score for screening sleep-disordered breathing - Peng, Min; Chen, Riken; Cheng, Junfen; Li, Jieying; Liu, Wang; Hong, Cheng (Journal of Thoracic Disease, 2018)
Background: Diagnosis of sleep-disordered breathing (SDB) requires overnight polysomnography (PSG). Because of the cost and low availability of these procedures, the NoSAS score was developed to identify subjects at high risk of SDB. To evaluate the clinical utility of the NoSAS score for screening patients with SDB in China and to compare the predictive value of the NoSAS score with the Epworth Sleepiness Scale (ESS), we used the STOP-Bang questionnaire and the Berlin questionnaire. Methods: In our study, we retrospectively reviewed the existing clinical data of patients who underwent an overnight PSG for suspected SDB from June 2014 to September 2017 at the sleep medical center of Guangdong Medical University Affiliated Second Hospital. The information we collected included all parts of the NoSAS score, the ESS, the STOP-Bang questionnaire and the Berlin questionnaire. Based on the severity of SDB determined by the apnea-hypopnea index (AHI), the patients were classified into four groups of primary snoring (30 events/h, the sensitivity and specificity were 0.590 and 0.707, 0.649 and 0.626, and 0.644 and 0.562, respectively; for the STOP-Bang questionnaire, the values were 0.721 and 0.512, 0.752 and 0.440, and 0.763 and 0.399, respectively; and for the Berlin questionnaire, the values were 0.721 and 0.512, 0.752 and 0.440, and 0.763 and 0.399, respectively. Conclusions: The NoSAS score and the Berlin questionnaire both exhibited good predictive value for SDB patients. NoSAS is a more suitable questionnaire to use in clinic for the conveniences but the similar performance with another questionnaire.